'At Least We Can Lock the Door': Radical Domesticity in the Writing of Bernadette Devlin and Nell Mccafferty. (2nd January 2021) - Davies, Eli
Abstract : This article explores the relationship between life-writing, domestic space and cultural memory, discussing Bernadette Devlin's 1969 memoir The Price of My Soul, and Nell McCafferty's 1988 book Peggy Deery, an account of the life of the Derry-woman of the title. I draw on the work of memory studies scholars including Astrid Erll (2011 . Memory in Culture. Basingstoke: Palgrave Macmillan) on literature and the 'canon' of cultural memory and examine how such memory in Ireland has been informed by sentimentalized visions of women's experiences in the home. These versions are challenged by Devlin and McCafferty's feminist life-writing project; the home here is an explicitly political space, and I explore how it is described as such, drawing on the work of feminist theorist Silvia Federici (2012 . Wages Against Housework. In: Revolution at Point Zero: Housework, Reproduction, and Feminist Struggle. Oakland: PM Press, pp. 15–22) and critic Susan Fraiman (2017 . Extreme Domesticity: A View from the Margins. New York: Columbia University Press).